2020
DOI: 10.1101/2020.02.14.949214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PEA15loss of function and defective cerebral development in the domestic cat

Abstract: 26Cerebral cortical size and organization are critical features of neurodevelopment and human 27 evolution, for which genetic investigation in model organisms can provide insight into 28 developmental mechanisms and the causes of cerebral malformations. However, some 29 abnormalities in cerebral cortical proliferation and folding are challenging to study in laboratory 30 mice due to the absence of gyri and sulci in rodents. We report an autosomal recessive allele in 31 domestic cats associated with impaired ce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Khufu also is effective for mapping traits in domestic cats. Graff et al (2020) identified a mutation in PEA15 that leads to impaired cerebral cortical size in domestic cats by analyzing sequence data from a set of affected and unaffected individuals. We analyzed only the WGS data which included 3 obligate carriers and 2 affected cats and RNA-seq data including 7 affected cats and 4 unaffected cats (Figure S11).…”
Section: Resultsmentioning
confidence: 99%
“…Khufu also is effective for mapping traits in domestic cats. Graff et al (2020) identified a mutation in PEA15 that leads to impaired cerebral cortical size in domestic cats by analyzing sequence data from a set of affected and unaffected individuals. We analyzed only the WGS data which included 3 obligate carriers and 2 affected cats and RNA-seq data including 7 affected cats and 4 unaffected cats (Figure S11).…”
Section: Resultsmentioning
confidence: 99%
“…Whole genome sequencing (WGS) and whole exome sequencing (WES) are available for domestic cats as genomic diagnostic tools for their healthcare via the community-based 99 Lives Cat Genome Sequencing Consortium [4,5]. Consortium studies are defining new disease variants for well-recognized disease genes, thereby supporting established biomedical models, such as Niemann-Pick disease type C [6]; new variants in new genes for known diseases, such as disproportionate dwarfism, thereby providing new genetic considerations for undiagnosed patients [7]; and new variants for new diseases of conserved biological processes, such as brain development or cell migration and differentiation [8]. The cat's genomic tools and the 99 Lives Consortium have led to more rapid identification of causal disease and trait variants in cats, hence naturally occurring biomedical models, with~84 mutations causing diseases under negative selection and 44 desired variants under positive selection in cats and at least seven variants influencing one blood group (https://omia.…”
mentioning
confidence: 99%
“…Genome editing of induced pluripotent stems cells supports VUS studies by creating the “disease in a dish” [ 5 , 6 ]; however, information from other species, comparative genetics, remains an invaluable tool to decipher VUS physiological effects, thereby influencing their priority for investigation. The research by Graff and colleagues, “ PEA15 loss of function and defective cerebral development in the domestic cat , ” is a strong example of when the murine model just does not rise to the challenge [ 7 ], and the value of other species models is recognized.…”
mentioning
confidence: 99%
“…Based on the analysis of primary astrocyte cultures from knockout mice, phosphoprotein expressed in astrocytes-15 ( Pea15) has been known for decades to be expressed in astrocytes and normally functions to suppress tumor necrosis factor alpha (Tnfα)-induced apoptosis in these cells [ 8 ]. However, mice with Pea15- targeted mutations have normal brain size and morphology, contrary to a newly defined neurological model in domestic cats [ 7 , 9 ]. Thus, PEA15 was not strongly implicated in brain development.…”
mentioning
confidence: 99%